(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2000)
Two new Megalancosaurus specimens collected from the Norian (Late Triassic) Calcare di Zorzino (Zorzino Limestone) Formation (Bergamo, Lombardy, Northern Italy), and from the coeval Dolomia di Forni (Forni Dolostone) Formation (Udine, Friuli, North-eastern Italy) improve our knowledge of skeletal anatomy and mode of life of this genus. Morphology of observable skull elements and cervical vertebrae in one of the new specimens shows some resemblance to the possible Triassic bird Protoavis, while the postcranial skeleton of Megalancosaurus is completely non-avian. This may suggest that either Megalancosaurus and Protoavis developed a similar neck structure as a response to the same functional requirement, or that part of the disarticulated material ascribed to Protoavis may indeed belong to a Megalancosaurus-like reptile. Megalancosaurus shows a very high adaptation to arboreal life and a peculiar feeding strategy. Recent suggestions that Megalancosaurus may have been a glider and a possible model for bird ancestry are discussed. Some skeletal features of Megalancosaurus may indeed be interpreted as gliding adaptation, but evidence is weak, and if this reptile was a glider, however, its gliding bauplan should have been completely different from the one usually accepted for bird ancestors, showing instead more morphological similarities with gliding squirrels, phalangeriids and putative ancestors of bats and pterosaurs (according to a non cursorial model for these latter).